2007
DOI: 10.1308/003588407x205323
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Anti-Reflux Surgery is Effective in Obese Patients with Gastro-Oesophageal Reflux Disease

Abstract: INTRODUCTION Obesity has long been regarded as a risk factor for the development of gastro-oesophageal reflux disease (GORD). It has been claimed that surgical efficacy of laparoscopic anti-reflux operations is decreased in obese patients. The aim of this study was to assess whether laparoscopic anti-reflux surgery is effective in obese patients with GORD compared to non-obese patients. PATIENT AND METHODS A total of 366 patients (mean age 44 years; range, 12–86 years) underwent laparoscopic anti-reflux surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 21 publications
(25 reference statements)
4
35
0
Order By: Relevance
“…Following laparoscopic antireflux surgery, dysphagia has been reported to significantly improve from preoperative values [47,188,197,198,[200][201][202][203][204] (level II-III). Despite reports of improved dysphagia following surgery, postoperative dysphagia remains a significant problem, with reported reoperation rates ranging from 1.8 to 10.8% [33,34,38,39,143,196,[205][206][207] (level I-III) and endoscopic dilatation rates ranging from 0 to 25% [34,121,143,145,189,195,196,[208][209][210][211][212][213] (level I-III). Although perioperative and early postoperative dysphagia have been reported as high as 76% [191] (level II), the majority of studies show early and mid dysphagia rates, up to 1 year postoperatively, of less than 20% [33,34,38,39,44,47,120,122,189,191,192,195,196,199,200,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following laparoscopic antireflux surgery, dysphagia has been reported to significantly improve from preoperative values [47,188,197,198,[200][201][202][203][204] (level II-III). Despite reports of improved dysphagia following surgery, postoperative dysphagia remains a significant problem, with reported reoperation rates ranging from 1.8 to 10.8% [33,34,38,39,143,196,[205][206][207] (level I-III) and endoscopic dilatation rates ranging from 0 to 25% [34,121,143,145,189,195,196,[208][209][210][211][212][213] (level I-III). Although perioperative and early postoperative dysphagia have been reported as high as 76% [191] (level II), the majority of studies show early and mid dysphagia rates, up to 1 year postoperatively, of less than 20% [33,34,38,39,44,47,120,122,189,191,192,195,196,199,200,…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effectiveness of fundoplication in obese individuals (BMI [ 30kg/m 2 ) has been questioned due to higher failure rates [143,144] (level II-III) compared with normal-weight patients. Nevertheless, others have reported equivalent outcomes in obese and normal-weight individuals [145][146][147][148] (level II-III). Laparoscopic Roux-en-Y gastric bypass (LRYGB) is the most effective and advantageous treatment option for GERD in the morbidly obese patient [149,150], since it treats GERD effectively and provides the additional benefit of weight loss and improvement in comorbidities, and is therefore the procedure of choice by many experts [151][152][153][154][155][156] (level II-III).…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patient selection is essential to achieving a good outcome [27] . To date, few studies have examined the long-term efficacy and durability of traditional anti-reflux procedures such as Nissen fundoplication in the setting of severe obesity, and results have been conflicting [18][19][20][21][22] . It has been suggested that laparoscopic anti-reflux surgery is associated with a higher failure rate in obese patients because of intraoperative technical difficulties as well as increased intra-abdominal pressure postoperatively [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The management of GORD in obese patients remains contentious with no consensus or published guidelines. Data are conflicting regarding the long-term efficacy of fundoplication in obese individuals compared with normal weight counterparts [18][19][20][21][22] . Nevertheless, most surgeons would agree that treatment of GORD in obese and non-obese patients requires different strategies [23] .…”
Section: Introductionmentioning
confidence: 99%